2021
DOI: 10.1007/s13224-021-01587-7
|View full text |Cite
|
Sign up to set email alerts
|

A Quasi-Experimental Study to Compare the Effect of Respectful Maternity Care Using Intrapartum Birth Companion of Her Choice on Maternal and Newborn Outcome in Tertiary Care Centre

Abstract: Purpose of the StudyTraditionally during labour woman is supported by another woman. However, in hospitals, continuous support during labour has often become the exception rather than the routine. Worldwide, there is a growing concern about the disrespect and abuse of women seeking maternity care. This prompted us to decide to change the obstetric care practices by providing a birth companion of her choice to women during labour and compare their maternal and newborn outcomes with the data from the same instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Women who had a birth companion with them for as long as they wished scored higher on “Own capacity” ( p value 0.004). It could be that the birth companion’s emotional support boosted the women’s confidence during birth, a phenomenon reported in some recent studies from India [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Women who had a birth companion with them for as long as they wished scored higher on “Own capacity” ( p value 0.004). It could be that the birth companion’s emotional support boosted the women’s confidence during birth, a phenomenon reported in some recent studies from India [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 91%
“…It could be that the birth companion's emotional support boosted the women's confidence during birth, a phenomenon reported in some recent studies from India [33,34].…”
Section: Plos Onementioning
confidence: 84%
“…These results also support literature suggesting that integrating support persons may lead to improved maternal and neonatal health outcomes [ 14 ]. The benefits of social support provided by doulas and support persons during labor and delivery are well-known (e.g., fewer cesarean deliveries, fewer neonatal intensive unit admissions) [ 6 , 29 ], but most literature has proposed underlying psychosocial mechanisms, positing that support persons’ presence reduces the adverse consequences of fear and distress when women labor alone [ 6 ]. Our study highlights improved quality care as an additional mechanism as support persons can influence providers’ care delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Support persons can enhance communication between providers and women by expressing women’s concerns to providers and ensuring that providers’ directions are heard and understood. Furthermore, results suggest that support persons play an important role in newborn care [ 29 ] all women’s PC-ISP indicators were associated with increased newborn key practices. Support persons may aid families’ involvement in newborn care, allowing women to be aware of newborns’ well-being and care during their own postpartum care and recovery.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found evidence (albeit at a low level of certainty) of an association between adoption of respectful maternity care policies in hospital environments and reduced episiotomy rates [ 20 ]. Ensuring that women have a companion of choice during birth has also been shown to reduce unnecessary caesarean sections and episiotomies [ 21 ].…”
Section: Introductionmentioning
confidence: 99%